Comparative study on slaughter performance, meat quality, and rumen microbiota of Hainan Dong goat and its hybrid with Nubian goat - Shi, Huiyu; Zhang, Naifeng; Tu, Yan; Yun, Yanhong; Diao, Qiyu; Ma, Tao (Frontiers in Veterinary Science, 2024)
IntroductionThe Hainan Dong goat (DG) is a local meat breed widely raised in Hainan, China because of its good adaptability to local hot and humid weather. However, the growth rate of these DG is much slower than that of commercialised breeds improved in European countries, resulting in poor carcase characteristics, including smaller slaughter weight and carcase weight, which have become increasingly prominent. In recent decades, Nubian goats have been continuously imported into China to improve the production performance of local breeds.MethodsIn this study, the effects of breed on growth performance, carcase and meat quality, and ruminal microbiota were analysed in 40 goats, including 20 DGs and 20 hybrid F3 offspring generated by crossing the DG and Nubian hybrids (NH). All the goats were averagely aged 90 days and weighed at 11  ±  1.34  kg. They were assigned to two treatments, with three replicates per treatment. The two groups were fed the same diet for 90 days before slaughter.ResultsThe results showed that the average daily gain, F/G ratio, slaughter weight, and carcase weight of the NH group were higher than those of the DG group (p < 0.05). However, tube circumference, meat-to-bone ratio, and eye muscle pH were lower in the NH group than in the DG group (p < 0.05). The NH group showed a smaller fibre crosssectional area and fibre diameter, but a larger fibre density than the DG group (p < 0.05). Bacteroidetes and Firmicutes were the most dominant phyla in the two groups; however, the two breeds had different ruminal microbial communities.DiscussionIn the present study, the differences in growth performance between two groups of goats under the same feeding environment and feed conditions were compared. The correlation between feed sources and rumen flora has been demonstrated, and the results of this study show that the same diet has similar effects on rumen microorganisms, which in turn have related effects on growth and production performance.ConclusionIn summary, hybrids can improve the growth and slaughter performance of local breeds, which may be related to changes in the rumen microorganisms. This study revealed that crossbreeding of Nubian goats with Dong goats has the potential to be used in a wide range of applications owing to its effectiveness in increasing production efficiency.